A reduced time to surgery within a 'fast track' pathway for periampullary malignancy is associated with an increased rate of pancreatoduodenectomy. Issue 8 (August 2017) - Roberts, Keith J.; Prasad, Pooja; Steele, Yvonne; Marcon, Francesca; Faulkner, Thomas; Cilliers, Hentie; Dasari, Bobby; Abradelo, Manuel; Marudanayagam, Ravi; Sutcliffe, Robert P.; Muiesan, Paolo; Mirza, Darius F.; et al.
Abstract: Introduction: Pancreatoduodenectomy (PD) typically follows preoperative biliary drainage (PBD) despite PBD being potentially harmful. This study evaluated a pathway to avoid PBD within the framework of the UK's NHS. Method: A prospective observational study of jaundiced patients undergoing PD for periampullary cancer. A pathway to provide early surgery without PBD was introduced at the start of the study period. Results: Over 12 months 61 and 32 patients underwent surgery with and without PBD respectively; 95% of patients in the PBD group had been stented before referral. The time from CT scan to surgery was shorter in the no PBD group (16 vs 65 days, p < 0.0001). Significantly more patients underwent PD in the no PBD group (31/32 vs 46/61, p = 0.009) and venous resection (10/31 vs 4/46, p = 0.014). The sensitivity of initial CT scan to define borderline resectable disease was worse in the PBD group (91 vs 50%, p = 0.042). Conclusions: Early surgery to avoid PBD is possible within the NHS. By reducing the time to surgery it appears that more patients undergo potentially curative resection. It is desirable to understand why surgery without PBD is not performed routinely as are the development of strategies to support its more widespread practice.